2018
DOI: 10.1097/scs.0000000000004541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nasal Septal Surgery on Sleep Quality and Attention-Deficit/Hyperactivity Disorder

Abstract: Besides the functional improvement of septoplasty, a long-lasting improvement in the quality of life is observed in patients with that undergo this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The forest plots in Figure 5 represent the impact of surgical treatment for patients with NSD on patient-reported outcome measures and the AHI. Three studies 1,49,50 used the EpSS, and 3 studies 50-52 utilized the PSQI in assessment of sleep quality following septoplasty. A mean posttreatment difference of –3.2 (95% CI, –4.2 to –2.2; P < .00001) was established for the EpSS and –3.4 (95% CI, –6.1 to –0.6; P = .02) for the PSQI.…”
Section: Resultsmentioning
confidence: 99%
“…The forest plots in Figure 5 represent the impact of surgical treatment for patients with NSD on patient-reported outcome measures and the AHI. Three studies 1,49,50 used the EpSS, and 3 studies 50-52 utilized the PSQI in assessment of sleep quality following septoplasty. A mean posttreatment difference of –3.2 (95% CI, –4.2 to –2.2; P < .00001) was established for the EpSS and –3.4 (95% CI, –6.1 to –0.6; P = .02) for the PSQI.…”
Section: Resultsmentioning
confidence: 99%
“…Independently of the AR diagnosis, previous studies with different objective and subjective methods have demonstrated that a general improvement in nasal obstruction is achieved after STP. 8,9,11,[18][19][20] The results regarding determination of AR as a predictive factor for less improvement in STP have been contradictory in recent studies. Mondina et al studied 100 patients after STP, among whom 28 presented AR, using the NOSE and RhinoQoL questionnaires before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Symptoms like sneezing, itchy nose, ocular symptoms and nasal obstruction were evaluated using a visual analogue scale (VAS) and the clinical history. VAS scores were classified as mild (scores of 1-3), moderate (4)(5)(6) or severe (7)(8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations